Requirements for brand managers in Ukraine and the Czech Republic: Identification and comparison - Zuzana Wroblowská (Trends Economics and Management, 2018)
Purpose of the article: This paper represents a set of requirements placed on brand managers when they are first approached by recruiters in both Ukraine and the Czech Republic. Methodology/methods: To conclude a successful empirical research, Berelson's content analysis method was used to study the texts of recruitment advertisements on career portals. Statistical verification of the results was conducted using the Pearson chi-square test. Scientific aim: The primary goal of the research project was to examine the situation of brand manager positions offered in the researched labour markets and to provide answers to the questions arising from the research assumption: "Employers do not publish different requirements for candidates for the job of Brand Manager in Ukraine and the Czech Republic". Findings: The result of the actual research project in Ukraine confirmed a fundamental need for applicants for brand manager positions with work experience in marketing (51.4%), knowledge of marketing (33.8%), and experience in the field of the advertiser company's business (31.1%). The application of information technology was found to be the third most important requirement in Ukraine, at 48.6%, unless the requirements for personality traits and skills were taken into account. The assumption regarding the matching requirements for brand manager positions in the two countries was rejected on the basis of the statistical verification process. The statistical test confirmed the shift of requirements even for & = 0.001 in the tested groups of signs. Conclusions: The data gained by studying publicly available recruitment adverts in the selected regions of Ukraine provided information on the most frequently published requirements for the required education and professional competencies based on professional knowledge, skills and type and length of experience. Comparison of the relative frequencies of requirements for brand manager positions in Ukraine and the Czech Republic indicated differences.
Keywords: D83; M12; M31; M51; 650; brand manager; knowledge; product management; recruitment advertisement; technical competence; transferable skills